Sikap dan Norma Subjektif Terhadap Intensi Mengkonsumsi Produk - Adi Koncara; Radhi Abdul Halim Rachmat (Jurnal Riset Bisnis dan Investasi, 2017)
Characteristics that affect consumption behavior adolescents are often influenced by psychological factors. This study explores an intention based theory of Ajzen and Fishbein be a model of human behavior known as Theory of Reasoned Action (TRA). The object of the research is a high school student in Bandung. From the 100 questionnaires, research results show that the intention to consume a product is the partial effect on the student's attitude (such as strong, stylish, handsome, sociable, flexible, bold). While the intention is not partial effect on the subjective norms (such as friends, idol, family). Attitudes and subjective norms simultaneously do not effect to the intention to consume a product.